A stacked triboelectric nanogenerator coupled with elastomer and non-elastomer for mechanical energy harvesting and hand motion recognition. (1st December 2022) - Luo, Jianfeng; Su, Yuxiang; Zhang, Chuanqiang; Gu, Yunqing; Liu, Anguo; Li, Zhenhua; Feng, Wuwei; Zhao, Keyang
Abstract: It is common to improve the adaptability and contact effect by using elastomer materials to fabricate triboelectric nanogenerator (TENG). However, compared with the traditional TENG made of non-elastomer, the existing design still has the disadvantages of low output and cumbersome preparation. This study proposes a TENG based on stacking teflon (PTFE), fluoro rubber (FKM), and polyurethane sponge (PU), the TENG not only combines the advantages of an elastomer and non-elastomer but also integrates the triboelectric characteristics of three materials to achieve higher performance. The stacked PTFE/FKM/PU TENG in single-electrode mode achieves a maximum instantaneous open-circuit voltage of 1250 V and short-circuit current of 108.9 μA, driving more than 1000 LEDs. It can also effectively recognize motion of flapping, wiping, squeezing, scratching, clicking, or poking by specific output feedback. Therefore, the stacked PTFE/FKM/PU TENG is expected to contribute to collection of discrete energy and development of human sensing technology. Graphical Abstract: ga1 Highlights: A stacking structure makes the TENG obtain better triboelectric characteristics. The TENG inherits the elastic deformation capacity of PU. In single electrode mode, the TENG also has strong output and applicability. Just in contact with human skin, more than 1000 LEDs can be driven by the TENG. The TENG can produce obvious output feedback for different hand movements.